Tungiasis-related life quality impairment in children living in rural Kenya. - Susanne Wiese; Lynne Elson; Hermann Feldmeier (Public Library of Science (PLoS), 2018)
Tungiasis (sand flea disease) is a neglected tropical skin disease caused by female sand fleas (Tunga spp.) embedded in the skin of the host. The disease is common in sub-Saharan Africa and predominantly affects children living in impoverished rural communities. In these settings tungiasis is associated with important morbidity. Whether tungiasis impairs life quality has never been studied.The study was performed in 50 children with tungiasis, living in resource-poor communities in coastal Kenya. Based on the Dermatology Life Quality Index (DLQI) a tool was developed to determine life quality impairment associated with tungiasis in children, the tungiasis-related Dermatology of Life Quality Index (tungiasis-related-DLQI). Pain and itching were assessed using visual scales ranging from 0-3 points. The intensity of infection and the acute and chronic severity of tungiasis were determined using standard methods.Seventy eight percent of the patients reported a moderate to very large effect of tungiasis on life quality at the time of the diagnosis. The degree of impairment correlated with the number of viable sand fleas present in the skin (rho = 0.64, p < 0.001), the severity score of acute clinical pathology (rho = 0.74, p < 0.001), and the intensity of pain (rho = 0.82, p < 0.001). Disturbance of sleep and concentration difficulties were the most frequent restriction categories (86% and 84%, respectively). Four weeks after curative treatment, life quality had improved significantly. On the individual level the amelioration of life quality correlated closely with the regression of clinical pathology (rho = 0.61, p < 0.001).The parasitic skin disease tungiasis considerably impairs life quality in children in rural Kenya. After effective treatment, life quality improves rapidly.